Aligning technology and institutional readiness: the adoption of innovation. Issue 10 (3rd October 2019) - Webster, Andrew; Gardner, John
ABSTRACT: This paper explores and develops the concept of 'readiness' as it relates to the adoption of innovation. In particular, the paper discusses readiness in regard to the notion of 'technology readiness' levels, widely used today by both producers and users to monitor and manage emergent innovation. The paper argues that, while useful, this notion needs to be informed by and subsumed within a broader concept of 'institutional readiness'. The latter is especially important in conceptualising how new technologies are actually adopted in organisational settings. The paper develops a model of institutional readiness that recognises the saliency of technology readiness but which embeds it within a broader socio-technical framework. This is illustrated with reference to the emerging field of regenerative medicine.